A simple halide and silver-free synthesis of Echavarren's catalyst directly from gold powder. Issue 4 (5th January 2018) - Albayer, Mohammad; Corbo, Robert; Hill, Anthony F.; Dutton, Jason L.
Abstract : A simple synthesis of Echavarren's catalyst via oxidation of gold powder with [NO][BF4 ] in acetonitrile followed by addition of Johnphos is presented. Abstract : An expedient procedure is reported for the preparation of the synthetically valuable Au(i ) complex [Au(MeCN)(P t Bu2 C6 H4 Ph-2)][BF4 ] (Echavarren's catalyst) directly from gold powder using [NO][BF4 ] in acetonitrile. The synthetic method obviates the potential presence of silver or halide impurities that follow from the tedious conventional synthesis, and have otherwise been shown to moderate catalyst performance.